Field work practice in urban slums: Issues and challenges in a megapolis of India - Asiya Nasreen; Ashvini Kumar Singh (Social Work and Society, 2020)
The practical learning through fieldwork is an integral part of social work education and practice. Learning by doing is the most acceptable methodology. Fieldwork practice facilitates the future of social work professionals through competent training facilities and developing appropriate skills and competencies. It provides an opportunity and exposure to working in various settings to the students.